Disability visibility : first-person stories from the twenty-first century - Wong, Alice, 1974- (Vintage Books, a division of Penguin Random House LLC, 2020)
"A groundbreaking collection of first-person writing on the joys and challenges of the modern disability experience: Disability Visibility brings together the voices of activists, authors, lawyers, politicians, artists, and everyday people whose daily lives are, in the words of playwright Neil Marcus, "an art . . . an ingenious way to live." According to the last census, one in five people in the United States lives with a disability. Some are visible, some are hidden--but all are underrepresented in media and popular culture. Now, just in time for the thirtieth anniversary of the Americans with Disabilities Act, activist Alice Wong brings together an urgent, galvanizing collection of personal essays by contemporary disabled writers. There is Harriet McBryde Johnson's "Unspeakable Conversations," which describes her famous debate with Princeton philosopher Peter Singer over her own personhood. There is columnist s. e. smith's celebratory review of a work of theater by disabled performers. There are original pieces by up-and-coming authors like Keah Brown and Haben Girma. There are blog posts, manifestos, eulogies, and testimonies to Congress. Taken together, this anthology gives a glimpse of the vast richness and complexity of the disabled experience, highlighting the passions, talents, and everyday lives of this community. It invites readers to question their own assumptions and understandings. It celebrates and documents disability culture in the now. It looks to the future and past with hope and love"--